Stable carbon, nitrogen, and oxygen isotope analysis as a potential tool for verifying geographical origin of beef - Nakashita, Rumiko; Suzuki, Yaeko; Akamatsu, Fumikazu; Iizumi, Yoshiko; Korenaga, Takashi; Chikaraishi, Yoshito (Analytica chimica acta, 2008)
Stable isotope analysis of organic elements such as carbon and nitrogen has been employed as a powerful tool for provenance determination of food materials, because isotopic compositions of the materials reflect many factors in natural environment. In this study, we examined carbon, nitrogen, and oxygen isotope signatures of beef from Australia, Japan, and USA, in order to confirm the method as a potential tool for verifying geographical origin of beef commercially distributed in Japan. Defatted dry matter of beef from USA was characterized by higher carbon isotopic composition (−13.6‰ to −11.1‰) than that from Japan (−19.6‰ to −17.0‰) and Australia (−23.6‰ to −18.7‰). That from Australia was characterized by higher oxygen isotopic composition (+15.0‰ to +19.4‰) than that from Japan (+7.3‰ to +13.6‰) and USA (+9.5‰ to +11.7‰). The oxygen isotopic composition in Japanese beef showed a positive correlation with the isotopic composition of cattle drinking water, the difference in which is clearly latitude dependent. These results suggest that a comparison of carbon, nitrogen, and oxygen isotopic compositions is applicable as a potential tool to discriminate the provenance of beef not only between different countries (i.e. Australia, Japan, and USA) but also among different regions within Japan.